2015
DOI: 10.1007/s11629-013-2795-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns and associations of dominant tree species in a mixed coniferous-broadleaf forest in the Changbai Mountains

Abstract: In 2012 a plot was established with 1-ha area in a mixed coniferous-broadleaf forest in the Changbai Mountains, northeastern China for examining local forest processes, structure and succession. A method of O-ring statistics (paircorrelation function) was applied to analyze the spatial patterns and associations of the dominant species within different vertical layers. After the evaluation by their importance values, six tree species (or group) (i.e. Abies nephrolepis, Picea jezoensis, Pinus koraiensis, Tilia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…The dominance of associated species, especially in community I, agreed well with studies at other sites 42 . Many of these species were also important in defining changed pathways.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The dominance of associated species, especially in community I, agreed well with studies at other sites 42 . Many of these species were also important in defining changed pathways.…”
Section: Discussionsupporting
confidence: 86%
“…Although many species were present on the Loess Plateau, our results showed that the interspecific association with an extremely significant level was low, and the results were consistent with the findings in the subtropical evergreen broadleaf forest 24 . The dominance of associated species, especially in community I, agreed well with studies at other sites 42 . Many of these species were also important in defining changed pathways.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The landscape is hilly, with forests at altitudes between 300 and 1200 m. The mean monthly temperature is 3.9°C, and the cumulative temperature above 10°C is approximately 2473°C. The annual precipitation is 500-600 mm, and the annual number of frost-free days is 110-130 d. The region has 170 days of snowfall from November to April (Li et al, 2013;Zhang et al, 2015). The soil is brown podzol.…”
Section: Study Areamentioning
confidence: 99%